Tangke mga gunita ng pagkabata - Jarin, Ferdinand Pisigan (Manila University of Santo Tomas Publishing House, 2020)
Collection of essays on various aspects of life.
Tangke -- Lumboy -- Kumbulsiyon -- Bagong damit -- Dugyot -- Lugaw -- Mangga -- Puto -- Floring -- Mama -- Papa -- Regalo.
Keywords: Philippine essays (Filipino); Autobiographical memory in literature